2016
DOI: 10.1093/mnras/stw2351
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and vorticity in Galaxy clusters generated by structure formation

Abstract: Turbulence is a key ingredient for the evolution of the intracluster medium, whose properties can be predicted with high resolution numerical simulations. We present initial results on the generation of solenoidal and compressive turbulence in the intracluster medium during the formation of a small-size cluster using highly resolved, non-radiative cosmological simulations, with a refined monitoring in time. In this first of a series of papers, we closely look at one simulated cluster whose formation was distin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
155
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(173 citation statements)
references
References 70 publications
(123 reference statements)
18
155
0
Order By: Relevance
“…These result can be interpreted by noticing that the scale at which the efficiency of prediction of the simulated ICM is maximum is tentatively close to the typical scale of turbulent eddies in the simulated ICM (e.g. Vazza et al 2011aVazza et al , 2012Miniati & Beresnyak 2015;Vazza et al 2016b), to the typical correlation scale of observed and simulated magnetic fields (e.g. Xu et al 2009;Bonafede et al 2013), as well as to the scale of measured projected density fluctuations in X-ray (e.g.…”
Section: Efficiency Of Prediction: Which Scales Are Best To Predict Tsupporting
confidence: 52%
See 1 more Smart Citation
“…These result can be interpreted by noticing that the scale at which the efficiency of prediction of the simulated ICM is maximum is tentatively close to the typical scale of turbulent eddies in the simulated ICM (e.g. Vazza et al 2011aVazza et al , 2012Miniati & Beresnyak 2015;Vazza et al 2016b), to the typical correlation scale of observed and simulated magnetic fields (e.g. Xu et al 2009;Bonafede et al 2013), as well as to the scale of measured projected density fluctuations in X-ray (e.g.…”
Section: Efficiency Of Prediction: Which Scales Are Best To Predict Tsupporting
confidence: 52%
“…The ICM is known to host volume filling subsonic turbulence at all epochs, as result of gravity-driven random motions (e.g. Vazza et al 2011a;Miniati & Beresnyak 2015;Vazza et al 2016b). The kinetic energy is thus subject to complex fluctuations due to turbulence even on the ≈ 7.3 × 10 7 yr timescale.…”
Section: Statistical Complexity In the Non-radiative Runmentioning
confidence: 99%
“…Vazza et al, 2017; in the simulations presented here we use a fixed resolution approach, using large (≥ 1024…”
Section: Cosmological Magneto-hydrodynamical Simulationsmentioning
confidence: 99%
“…Ryu et al, 2008) and the vorticity squared (also known as ???enstrophy?? ?, (∇ × v) 2 ≡ ω ) gives a convenient way of estimating the turbulent dissipation rate on the fly in our simulations as F turb η t ρ 3 ω /L , where η t = 0.014 and L is the stencil to compute the vorticity (Jones et al, 2011;Porter et al, 2015;Vazza et al, 2017;Wittor, Jones, Vazza and Brüggen, 2017). The fraction of this turbulent kinetic power which is ultimately converted into magnetic energy, dyn , sets the amplified magnetic energy as E B,dyn = dyn (M)F turb ∆t.…”
Section: Appendix D Subgrid Dynamo Modelmentioning
confidence: 99%
“…Numerical simulations suggest that incompressible turbulence is important in the ICM (Miniati 2014;Vazza et al 2017). Turbulent reacceleration by large-scale incompressible turbulence in the ICM has been investigated in Brunetti & Lazarian (2016).…”
Section: Beyond the Case Of Collisionless Ttd Reaccelerationmentioning
confidence: 99%